Exploration of Indigenous Brown Algae Species of Lombok for Carageenan Sources - Widyastuti, Sri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Seaweed known as a producer of hydrocolloid compounds, including carageenan , an important raw material for many industries. Therefore, knowledge on the carageenan producing seaweeds is quiet important to support the carrageenan production in Indonesia. This article reports the carageenan content of local strains brown algae. Research was conducted by collecting all species of brown algae grow in Lombok, drying, extracting its carageenan using ethanol and isopropanol methods. Results showed that the carrageenan content of these species around 0,75 (Turbinaria ornata) - 6,92% (Dictyota sp.1). Unfortunately, these values are lower than that of the minimal carageenan content recommended by Indonesian Trade Department. The carrageenan content of these strains was not significantly different either extracted by ethanol or isopronol method. It is suggested that these strains are not carageenan producing seaweed. It needs further study to understand the type of hydrocolloid compound produced by brown algae species.Keywords: carageenan, ethanol extraction, isopropanol extraction, brown algae, Lombok